Preserving Cultural Heritage through Collaborative Design: A Participatory Action Research on Nakhon Silver Niello Jewelry in Thailand - Jedsada Suksikarn; Rewat Suksikarn (Journal of Visual Art and Design, 2026)
This research developed innovative Nakhon silver nielloware jewelry appealing to younger and professional demographics while safeguarding traditional craftsmanship through community-based collaboration. Utilizing participatory action research with Actor-Network Theory principles, twenty community members co-created two jewelry collections inspired by water droplets and "Nakhon Song Tham" symbolism. The designs achieved high consumer satisfaction (4.57/5.0) and successful commercialization with 52,000 THB revenue from initial market testing. Comprehensive knowledge preservation through multimedia documentation received 4.56/5.0 satisfaction ratings. The study demonstrates how participatory approaches can effectively balance cultural authenticity with commercial viability, contributing to UNESCO's safeguarding framework and Sustainable Development Goals 2030 for cultural sustainability.